English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Of the problem y=ln(cos(ln theta))

2007-11-01 02:11:32 · 2 answers · asked by The Anonymous 1 in Science & Mathematics Mathematics

2 answers

Use the chain rule

Let y=ln(u), u=cos(w), w=ln(theta)

So y = ln(cos(ln(theta)))

The chain rule says

dy/dtheta = dy/du du/dw dw/dtheta

y=ln(u), u=cos(w), w=ln(theta)

dy/du = 1/u du/dw = -sin(w) dw/dtheta = 1/theta

dy/dtheta = 1/u -sin(w) 1/theta

dy/dtheta = 1/cos(w) -sin(w) 1/theta

dy/dtheta = -sin(ln(theta))/cos(ln(theta)) 1/theta

dy/dtheta = -tan(ln(theta))/theta

2007-11-01 02:18:34 · answer #1 · answered by Astral Walker 7 · 0 0

1/cos(ln theta) * [-sin(ln theta)] * 1/theta = -tan(ln theta)/theta

2007-11-01 02:19:10 · answer #2 · answered by Amit Y 5 · 0 0

fedest.com, questions and answers